2021
DOI: 10.3389/fonc.2021.725336
|View full text |Cite
|
Sign up to set email alerts
|

Runt-Related Transcription Factor 3 Promotes Acute Myeloid Leukemia Progression

Abstract: Acute myeloid leukemia (AML) is an aggressive hematological malignancy with high relapse/refractory rate. Genetic and epigenetic abnormalities are driving factors for leukemogenesis. RUNX1 and RUNX2 from the Runt-related transcription factor (RUNX) family played important roles in AML pathogenesis. However, the relationship between RUNX3 and AML remains unclear. Here, we found that RUNX3 was a super-enhancer-associated gene and highly expressed in AML cells. The Cancer Genome Atlas (TCGA) database showed high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
1
6
1
Order By: Relevance
“…RUNX3 KD did not impact on cell growth. This is in contrast to a recent study that showed that RUNX3 KD inhibits AML progression in MLL::AF9 mice by inducing DNA damage and apoptosis [ 39 ]. Overall, RUNX3 KD did not affect the normal program of myeloid differentiation of human HSPC or AML cell growth, with the caveat that RUNX3 was not completely suppressed.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…RUNX3 KD did not impact on cell growth. This is in contrast to a recent study that showed that RUNX3 KD inhibits AML progression in MLL::AF9 mice by inducing DNA damage and apoptosis [ 39 ]. Overall, RUNX3 KD did not affect the normal program of myeloid differentiation of human HSPC or AML cell growth, with the caveat that RUNX3 was not completely suppressed.…”
Section: Discussioncontrasting
confidence: 98%
“…Nonetheless, survival analysis of non-CBF AML patients suggests that high RUNX3 levels remain associated with poor outcome. These findings support a recent study that identified RUNX3 as one of three super-enhancer associated genes that is abnormally overexpressed in AML cells compared to normal hematopoietic cells, such as neutrophils, monocytes, and HSPC [ 39 ]. In childhood AML, increased RUNX3 expression was associated with a shortened EFS and OS among patients [ 4 , 40 ].…”
Section: Discussionsupporting
confidence: 90%
“…The common TFs shared by SMGR’ and SOMatic's program, such as RUNX1 ( 43 ) and NFE2 ( 44 , 45 ), are known TFs that play important roles in leukemia. Meanwhile, some TFs which are known to be important in acute leukemia can only be identified by the SMGR’s program but not by SOMatic, for example, RUNX3 ( 46 , 47 ), SNAI1 ( 48 ) and THAP1 ( 49 ). Of note, SMGR reveals more regulators based on the co-regulatory program, suggesting the validity and superior performance of SMGR.…”
Section: Resultsmentioning
confidence: 99%
“…As a transcription factor, RUNX3 is bound to the promoter of cell cycle-related genes in both normal and AML cells. However, within AML cells, RUNX3 is also bound to the promoters of DNA repair genes ( CHEK1 , RAD51C , RPA2 , and DDB1 ), antiapoptotic genes ( BCL2 , BCL2L10 , BCL2L12 , and MCL1 ), and genes implicated in leukemogenesis ( MYC , CD93 , KIT , IKZF2 , FTO , and SOX4 ) [ 61 ] ( Figure 3 ). In this study, RUNX3 knockdown inhibited leukemic progression by inducing DNA damage and higher apoptosis.…”
Section: Runx3 Defects In Human Cancers and Genomic Instabilitymentioning
confidence: 99%